Tracheal bifurcation repair for blunt thoracic trauma in a patient with COVID-19 - Shoji Kuriyama; Kazuhiro Imai; Kasumi Tozawa; Shinogu Takashima; Ryo Demura; Haruka Suzuki; Yuzu Harata; Tatsuki Fujibayashi; Sumire Shibano; Yoshihiro Minamiya (Surgical Case Reports, 2023)
Abstract Background Tracheobronchial injury (TBI) is a rare but potentially life-threatening trauma that requires prompt diagnosis and treatment. We present a case in which a patient with COVID-19 infection was successfully treated for a TBI through surgical repair and intensive care with extracorporeal membrane oxygenation (ECMO) support. Case presentation This is the case of a 31-year-old man transported to a peripheral hospital following a car crash. Tracheal intubation was performed for severe hypoxia and subcutaneous emphysema. Chest computed tomography showed bilateral lung contusion, hemopneumothorax, and penetration of the endotracheal tube beyond the tracheal bifurcation. A TBI was suspected; moreover, his COVID-19 polymerase chain reaction screening test was positive. Requiring emergency surgery, the patient was transferred to a private negative pressure room in our intensive care unit. Due to persistent hypoxia and in preparation for repair, the patient was started on veno-venous ECMO. With ECMO support, tracheobronchial injury repair was performed without intraoperative ventilation. In accordance with the surgery manual for COVID-19 patients in our hospital, all medical staff who treated this patient used personal protective equipment. Partial transection of the tracheal bifurcation membranous wall was detected and repaired using 4-0 monofilament absorbable sutures. The patient was discharged on the 29th postoperative day without postoperative complications. Conclusions ECMO support for traumatic TBI in this patient with COVID-19 reduced mortality risk while preventing aerosol exposure to the virus.